2003
DOI: 10.1167/iovs.02-0493
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Antithrombin III on Interactions between Blood Cells and Endothelial Cells during Retinal Ischemia–Reperfusion Injury

Abstract: This study demonstrates the inhibitory effects of AT III on leukocyte and platelet recruitment to the postischemic retina, which may account for the neuroprotective properties of this alpha-2 globulin against retinal ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
2
28
0
1
Order By: Relevance
“…A relationship between neutrophil accumulation at inflammatory sites and platelets has become apparent in several tissues 8 -11 including other ocular tissues. 12,13 We found that antibody-induced depletion of circulating neutrophils significantly reduced platelet localization in the limbal vessels, and depletion of blood platelets reduced neutrophil accumulation. 6 In the current study, we investigate the contributions of T cells to the healing and inflammatory events after corneal epithelial abrasion.…”
mentioning
confidence: 77%
“…A relationship between neutrophil accumulation at inflammatory sites and platelets has become apparent in several tissues 8 -11 including other ocular tissues. 12,13 We found that antibody-induced depletion of circulating neutrophils significantly reduced platelet localization in the limbal vessels, and depletion of blood platelets reduced neutrophil accumulation. 6 In the current study, we investigate the contributions of T cells to the healing and inflammatory events after corneal epithelial abrasion.…”
mentioning
confidence: 77%
“…Therefore, it is possible that the number of IRIs could be reduced if production of these factors could be suppressed. Corticosteroids inhibit the production of various inflammatory molecules [17][18][19] that promote leukocyte adhesion and breakdown of the blood-retinal barrier [20,21] . In addition, Fan et al [22] reported that the mean number of doses was significantly higher with IRI alone than with IRI plus intravitreal triamcinolone acetonide.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the results of these experiments, many investigators have studied various agents that can attenuate tissue damage by suppressing leukocyte-endothelial interactions in the postischemic retina. Antithrombin III [83,84], tacrolimus (FK506) [85], argatroban (direct thrombin inhibitor) [86], statin [87,88], Rho-associated protein kinase inhibitor [89], superoxide dismutase [90], thalidomide [91], selectin ligands/inhibitor (SKK-60060) [92], triamcinolone acetonide [93], ischemic preconditioning [94,95], platelet depression [81], and 17β-estradiol [96] are reported to reduce leukocyte accumulation in the postischemic retina and thereby reduce neural damage.…”
Section: Leukocyte-endothelial Interactions In Pathological Conditionsmentioning
confidence: 99%